Aplicação e análise de métodos de custeio para a redução dos custos de uma fábrica de palmito de açaí em conserva - RODRIGUES, Joilson Rodrigues e (2022)
In an increasingly competitive market, where the prices of products adopting almost fixed behavior, it is important that companies perform a good management of their costs, so that they can remain competitive and profitable. This study had the intention of propose some alternatives for the reduction of costs and waste of a company that manufactures canned açaí palm hearts, through the analysis of the data generated with the implementation of the ABC and Variable costing methods in the most productive period of the factory. Regarding the methodologies used, the research had a applied purpose, qualitative and quantitative approach, exploratory and descriptive objective, and used the documentary procedure to study the company's files that were assigned for the research, and the case study procedure, for conducting a 3-month follow-up at the factory, in order to collect the other base data for the implementation of the costing methods. With the application of costing methods at the factory, it became possible to obtain relevant information for cost management, such as the costs of activities and products, contribution margin, break-even point and others. Through the analysis of these data and the unproductive of the factory, it was possible to make suggestions for the reduction of its costs and waste. Subsequently, a 5W1H action plan was elaborated to synthesize the proposed alternatives, answering important questions for the execution of these proposals, which aim to reduce the company's expenses and increase its profit.